Prevasive Healthcare and Machine Learning Algorithms - Nikam, Swati S; Pawar, Veena R; Kshirsagar, Jyoti P; Bagwan, Ali Akbar (International Journal of Computer Sciences and Engineering, 2025)
In Healthcare, prevention and cure have seen diverse advancement in technological schema. Chronic care and prevention care both stand on equal level with the same advancement in technology. We propose PREVASIVE method towards healthcare diagnosis. The word ‗EVASIVE‘ means ‗something which is intended to come‘. The prosing word ‗PERVASIVE‘ is to mean prevention against the one which is intended to come. In medical history, technology contributes towards diagnosis through machine learning algorithms. Machine learning algorithms are also applied for prediction towards prevention of various diseases and this in course help for cure for specific disease. We propose diagnosis of health through inheritance traits and surroundings the person inhibits from. For knowledge, inheritance traits, history of the person is collected as PHR (Personal Health Record). The GPS (Global Positioning System) module is used to see where the person inhibits. Location and movement of person is taken into consideration to know if the region has the history of any specific diseases‘ and GPS module applied with appropriate machine learning algorithms can help us determine diagnosis for diseases which are intended to come towards the specific person.